From Accountability to Trust: Strengthening Zakat Institutions in Emerging Economies - Noor Riefma Hidayah; Andi Mattulada; Muliati (Invoice : Jurnal Ilmu Akuntansi, 2026)
Despite the substantial potential of zakat in Indonesia, limited trust among zakat payers (muzakki) remains a critical barrier to optimizing its collection and institutional effectiveness. This study examines the influence of internal control systems, zakat accounting standards, and human resource competence on muzakki trust, with accountability positioned as a moderating variable. Grounded in Sharia Enterprise Theory and governance perspectives, this research adopts a quantitative approach using survey data collected from 102 employees of zakat institutions, including BAZNAS and LAZNAS. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both measurement and structural models. The findings reveal that internal control systems, zakat accounting standards, and human resource competence each have a positive and statistically significant effect on muzakki trust. Furthermore, accountability consistently strengthens these relationships, confirming its role as a critical reinforcing mechanism that enhances the effectiveness of governance practices. These results indicate that trust is not solely driven by religious obligation but is significantly shaped by stakeholders’ rational evaluation of transparency, professionalism, and institutional credibility. This study contributes to the literature on Islamic philanthropy and nonprofit governance by integrating multiple governance dimensions within a unified framework and positioning accountability as a moderating construct. The findings offer practical implications for zakat institutions and policymakers to strengthen governance structures, improve reporting quality, and enhance human resource capacity to foster sustainable public trust in emerging economies.